Analysis of Javanese Ngapak Banyumasan As Part of Indonesian Literature - Mustakimah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Language is an important factor in human life, especially as a shaper of culture and mindset. Language, culture and thought as three factors that affect one's life. Each region in the territory of the Unitary State of the Republic of Indonesia has its own linguistic characteristics which are then referred to as regional culture and literature which must be preserved. The method used in preparing this article is observation in the form of interviews with informants supported by literature. The data obtained is in the form of a descriptive translation of the Javanese Ngapak language in its application in the daily life of Banyumas residents who are known by the general public in Indonesia with their thick Javanese dialect. The Javanese Ngapak language is spoken by the people of Banyumas by paying attention to the interlocutor by using the appropriate intonation.